DNA is replicated at the nuclear cage. - McCready, S; Godwin, J; Mason, D; Brazell, I; Cook, P (1980)
Structures resembling nuclei are released when HeLa cells are lysed in a detergent and 2 M salt. These nucleoids, which lack any organized membrane structure, contain all the nuclear DNA packaged within a cage of RNA and protein. Their DNA is supercoiled so that the linear DNA must remain unbroken and looped during lysis. Following digestion with the restriction endonuclease, EcoRI, cages and associated DNA were filtered free of unattached DNA. Pulse-labelled (i.e. newly synthesized) DNA remains preferentially associated with the cages. This association has been confirmed by autoradiography. When nucleoids are prepared for electron microscopy by the Kleinschmidt procedure the DNA spills out to form a skirt around the flattened cage. Labelling, which is restricted to the region of the cage after short pulses, extends out into the skirt as the labelling time increases. A model, based on the premise that replication takes place at the nuclear cage, is presented in the Appendix. The results of the biochemical experiments and electron microscopy both indicate that the average size of the unit of replication is approximately 2 micrometer. This is about one-quarter the size of the average structural unit - the loop. Therefore sequences in the loop must become attached to the nuclear cage prior to the initiation of DNA synthesis.